Cuproptosis: Cellular and molecular mechanisms underlying copper-induced cell death - Cobine, Paul A; Brady, Donita C (Molecular cell, 2022)
Tsvetkov et al. (2022) discovered a new form of cell death triggered by targeted accumulation of Cu in mitochondria that drives lipoylated TCA cycle enzyme aggregation via direct Cu binding.Tsvetkov et al. (2022) discovered a new form of cell death triggered by targeted accumulation of Cu in mitochondria that drives lipoylated TCA cycle enzyme aggregation via direct Cu binding.